"They take care of their own": healthcare professionals' constructions of Sami persons with dementia and their families' reluctance to seek and accept help through attributions to multiple contexts. Issue 1 (1st January 2017) - Blix, Bodil Hansen; Hamran, Torunn
ABSTRACT: Background : Norwegian government white papers have stated that the Sami population is reluctant to seek help from healthcare services and has traditions of self-help and the use of local networks. Objective : In this article we explore healthcare professionals' discursive constructions of Sami persons with dementia and their families' reluctance to seek and accept help from healthcare services. Design : The article is based on an analysis of focus group interviews with healthcare professionals (n = 18) in four municipalities in Northern Norway with multiethnic populations. A narrative context analysis, which involved an examination of sequences of discourse, was employed. Results : Reluctance to seek and accept help among Sami service users and assumptions about self-support were recurring themes in the focus groups. The reluctance was attributed to macro contexts, such as socio-historical processes and cultural norms, and to micro contexts, such as individual and interpersonal factors including the healthcare professionals' cultural backgrounds and language competence. The healthcare professionals' positioning as insiders or outsiders (Sami or non-Sami) affected their attributions. Conclusions : Local healthcare professionals are at the front line for providing and assessing service users' needs for healthcare services. Consequently, their perceptions of service users' needs are pivotal for achieving equity in healthcare. The established opinion that Sami "take care of their own" and are reluctant to seek and accept help may lead to omissions or neglect. Healthcare professionals' awareness about how present encounters in healthcare settings are framed and shaped by the service users' previous and prevailing experiences of marginalisation and subordination is crucial to avoid omissions or neglect resulting from assumptions about cultural preferences. Discursively shaped boundaries and differences between groups may create the impression that the distance between the groups is too wide to traverse, which in turn may lead to further marginalisation of service users in healthcare encounters.